Relevance of Objectives, Activities, and Learning Media in the Learning Plan at RA Bani Adam Boyolali - Anggraini, Dewi; Darsinah, D (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine (1) the relevance between learning outcomes and learning activities, (2) the relevance between learning activities and media, and (3) the alignment among objectives, activities, and learning media in the context of early childhood education at RA Bani Adam Boyolali. Methodology: A qualitative content‐analysis design was employed, using RPPH (Daily Learning Implementation Plans) as the primary data source. Researchers extracted and examined documented learning objectives, activities, and media, and supplemented this with interviews. The analytic process involved formulating research questions, selecting and identifying relevant documents for review, and drawing conclusions based on observed patterns of relevance. Results: Out of 57 learning objectives and 53 activities, 49 activities (92.5%) matched their intended objectives, while 4 activities (7.5%) did not. In terms of media support, 46 out of 53 media items (86.7%) were deemed relevant to the corresponding play‐based activities, leaving 7 media items (13.3%) misaligned. Finally, when considering the triadic relationship among objectives, activities, and media, 44 media items (83.0%) supported both the core activities and their objectives, whereas 9 items (17.0%) failed to align across all three dimensions. Applications/Originality/Value: By systematically mapping alignment among objectives, activities, and media, this study provides a replicable framework for early childhood educators to audit and refine their daily learning plans. The high rates of alignment observed underscore the effectiveness of RA Bani Adam’s current practice, while the identified gaps highlight specific areas—such as media selection and activity design—where targeted adjustments and professional development can further enhance teaching quality and learning outcomes.